Effects of gamma oryzanol supplementation on anthropometric measurements & muscular strength in healthy males following chronic resistance training - Eslami, Saghar; Mohd Esa, Norhaizan; Marandi, Seyed Mohammad; Ghasemi, Gholamali; Eslami, Sepehr (Wolters Kluwer – Medknow, 2014)
Background & objectives: Enhanced muscle strength is seen when resistance exercise is combined with the consumption of nutritional supplements. Although there is a limited number of studies available about the efficacy of gamma oryzanol supplementation with resistance exercise in humans, but its usage as a nutritional supplement for strength is common in athletes. The aim of this study was to determine the effects of gamma oryzanol supplementation during 9-week resistance training on muscular strength and anthropometric measurements of young healthy males. Methods: In this double-blind clinical trial, changes of anthropometric measurements and muscular strength were studied after chronic resistance exercise and gamma oryzanol supplementation in 30 healthy volunteers (16 in supplement and 14 in placebo). Each day, gamma oryzanol supplement (600 mg) and placebo (the same amount of lactose) were consumed after training. The participants exercised with 80 per cent 1-Repetition Maximum (1-RM), for one hour and four days/week. Anthropometric measurements and subjects’ 1-RM for muscular strength were determined at the commencement and end of the 9-week study. Results: There was no significant difference between the baseline characteristics and target variables at baseline between the two groups. After gamma oryzanol supplementation, there was no significant difference in the means of anthropometric and skin fold measurements between the supplement and placebo groups. However, there were significant differences between the supplement and placebo groups for 1-RM of bench press and leg curl, which showed that gamma oryzanol improved muscle strength following resistance training. Interpretation & conclusions: Our findings indicated that 600 mg/day gamma oryzanol supplementation during the 9-week resistance training did not change anthropometric and body measurements, but it increased muscular strength in young healthy males. Further, studies need to be done in trained athletes, women, and in patients who suffer from muscular fatigue.